(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Globally, Monosodium glutamate (MSG) is a flavor enhancer that is used all over the world. MSG is an umami-flavored flavor enhancer. Together with salty, sour, bitter, and sweet, umami is the fifth basic taste. MSG is utilized in the food sector as a flavor enhancer with an umami taste that increases the fleshy, savory taste of food, much like glutamate that occurs naturally in foods like stews and meat soups. Many studies have been done on the safety of MSG, which has been used to season food for more than a century. Humans can metabolize relatively large amounts of glutamate under normal circumstances because exopeptidase enzymes naturally produce it in the gut during the hydrolysis of proteins. MSG is still consumed in large quantities even though its safety has been called into question. This paper contributes to our understanding of the molecular pathways, such as the umami taste signaling pathway and different brain glutamate regulation mechanisms, that underlie MSG-induced neurotoxicity. MSG has been connected to obesities, metabolic diseases, Chinese restaurant syndrome, neurotoxic and negative effects on reproductive organs. Studies conducted on both humans and animals have shown that even trace amount of MSG are harmful. The recommended daily intake of MSG is 0.3–1.0 g. This study uses recent and historical data from investigations on humans and animals to review a few common harmful effects of MSG on the body organs. The future application of MSG, as well as actions taken and potential dietary substitutions for MSG to remove its toxicity and related public health concerns, are all covered in this study. The conclusion was that MSG should be avoided in diets as much as possible because it is more harmful than helpful to the general public’s health.